CODE SWITCHING IN THE SONGS MISSING AND SPECIAL KISS BY NANIWA DANSHI - Reynaldi, Vito Faisal; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to describe code-switching in the lyrics of the songs Special Kiss and Missing. The subject of this research is the song entitled Special Kiss and Missing Song by Naniwa Danshi. The object of this research is the code-switching contained in these two songs. The qualitative method was employed in the study is descriptive, Specifically, referring to research utilizing descriptive analyses presented through song lyrics. The songs "Special Kiss" and "Missing" exhibit instances of external code-switching from Japanese to English. The findings of this study highlight distinct characteristics that emerge from analyzing these two songs: 1. The analysis reveals the utilization of two types of code-switching in the two songs. 2. In "Special Kiss," intra-sentential code-switching is frequently employed, whereas in "Missing," inter-sentential code-switching is more prevalent 3. In these two songs, intra-sentential code-switching predominates, with 12 instances compared to inter-sentential code-switching, which only occurs 7 times